IAP accelerator based facility for simulation and studies of radiation induced defects in materials - Storizhko, V.Yu. (Вопросы атомной науки и техники, 2009)
Report presents the programme and status of the works conducting at IAP NASU on the creation of the nanoanalytical center based on the electrostatic accelerators. The main purpose of the center is to investigate structure and composition of the reactor materials as well as to validate computer modeling of the radiation defects. Представлено програму та стан робіт, що проводяться в Інституті прикладної фізики по створенню наноаналітичного центру з використанням електростатичних прискорювачів. Головною метою центру є вивчення структури та складу реакторних матеріалів, а також комп’ютерне моделювання радіаційних дефектів. Представлены программа и состояние работ, проводимых в Институте прикладной физики по созданию наноаналитического центра с использованием электростатических ускорителей. Главной целью центра является исследование структуры и состава реакторных материалов, а также компьютерное моделирование радиационных дефектов.